Risk Analysis and Mitigation in Supply Chain at PT. XYZ with Best Worst Method and House of Risk - Ariyanti, Fredika Aura Kusuma; Pulansari, Farida; Dewi, Sinta (Journal La Multiapp, 2025)
Risk is a known uncertainty while uncertainty is an unknown risk. Risk can only be reduced by risk management. The purpose of this study is to solve the problems at PT. XYZ in the field of LPG tank product manufacturing. The problems experienced by the company are frequent material delays and overproduction. In this study, the problem-solving methods used are the BWM and HOR methods. The results of the study found that material delays are the main risk and with mitigation s trategies to improve supplier selection criteria.